Switching rights. About how the Anti-Trafficking Campaign eliminated a category of female workers - Daich, Deborah (Revista de Antropología Social, 2022)
Since the Argentinian trafficking law was reformed in 2012, almost all matters related to the sex market have been tinged with suspicion and read in terms of violence. Thus, in the name of combating trafficking, in 2016 the City of Buenos Aires banned an old and recognized job category: female employees hired to make conversation or dance with nightclubs´clients and encourage them to buy expensive drinks. In the legislators' discourse, this occupation was understood as prostitution (and therefore as a case of violence against women), as well as a facade for human trafficking. How was it that the anti-trafficking campaign was able to eliminate this category without major repercussions? What happened to the workers and their union? What did feminisms have to say about it? This paper tries to answer these questions based on a fieldwork carried out between 2013 and 2019.
Keywords: sex market; anti-trafficking campaign; copperas